A suggestion that Europe is the Muslim Domain: a study from historical and contemporary perspectives - Muhammad Aiman Awaluddin; Anisa Safiah Maznorbalia (Indonesian Journal of Islam and Muslim Societies, 2019)
In the past century saw that Europe associates themselves as a Christian domain until now. The proclamation of Edict of Thessalonica in 380 AD made Nicene Christianity as the state in The Roman Empire and saw a transition from paganism to a Christian domain of Christendom. Since its inception, several edicts have been enacted and several peace treaties have been broken to diminish an idea of multiculturalism within their faith land. The establishment of Muslim rules in the Iberian Peninsula has changed the dominion of Christian. Muslims in Spain introduced convivencia, which saw that Abrahamic religions, Islam, Judaism, and Christianity co-exist together, removing racial, cultural, and religious barriers to embrace each other that nurture spirit of inclusion. The Golden Age of Muslim Civilization gives a piece of evidence that Cordova has become a center of Europe, perhaps the world for scientific knowledge advancement. Subsequently, it contributes to the Renaissance Age in Europe. Additionally, the fall of Constantinople in 1453 under Ottomans reshaping the geography of Europe and permanently marked the term of European Islam. Through tedious analysis of media, reports, and past journals, this article adopted critical analysis in understanding the complexity of the history of Europe, at the same time positioning Islam as part of European culture. The contribution of Islam in Europe seems negligible and less attention has been given. Past researchers tend to overlook and belittle impacts of Islam in the European continent, thus diminish any legitimacy of Islam in Europe. Critical analysis methodology assists the researcher to understand the main issues, review past and present evidence from reliable sources to establish concrete arguments in providing critical evaluation on the issues. It is also a form of the method involving the investigated topics more deeply, by going beneath the surface of reality to explore the truth of a particular issue. The article established its arguments through a historical analysis in Europe starting from ancient time to present situation to give a clear analogy and legitimacy on the presence of Islam in Europe. The finding shows that Islam indeed a part of Europe since the establishment of Umayyad Caliphate and the presence of Islam in Sicily. Moreover, contemporarily, the rising of Muslims, issues of atheism, and secularism prove that Europe is no longer the center of Christianity but already becomes a multicultural society. Pada abad lalu, Eropa mengasosiasikan diri mereka sebagai sebuah domain Kristen sampai sekarang. Maklumat Edict of Thessalonica pada 380 AD menjadikan Kekristenan Nicene sebagai negara di dalam Imperium Romawi dan melihat peralihan dari paganisme kepada suatu domain Kristen atau Kekristenan. Sejak didirikan, beberapa dekrit telah diberlakukan dan beberapa perjanjian damai telah dipatahkan untuk mengurangi gagasan multikulturalisme di dalam tanah kepercayaan mereka. Pendirian aturan Muslim di Semenanjung Iberia telah mengubah kekuasaan Kristen. Muslim di Spanyol memperkenalkan convivencia, yang melihat bahwa agama Abrahamik, Islam, Yudaisme dan Kristen hidup berdampingan bersama-sama, menghilangkan hambatan rasial,budaya dan agama untuk merangkul satu sama lain yang memupuk semangat inklusi. Zaman keemasan peradaban Muslim membuktikan bahwa Cordova telah menjadi pusat Eropa dan mungkin dunia untuk kemajuan pengetahuan ilmiah. Selanjutnya, berkontribusi untuk Renaissance Age di Eropa. Selain itu,jatuhnya Konstantinopel pada tahun 1453 di bawah Ottomans membentuk kembali geografi Eropa dan secara permanen menandai istilah Islam Eropa. Melalui analisa yang membosankan tentang media, laporan dan jurnal masa lalu, artikel ini mengadopsi analisa kritis dalam memahami kompleksitas sejarah Eropa, pada saat yang sama memposisikan Islam sebagai bagian dari budaya Eropa. Kontribusi Islam di Eropa tampaknya diabaikan dan kurang mendapatkan perhatian. Peneliti masa lalu cenderung mengabaikan dan meremehkan dampak Islam di benua Eropa, sehingga mengurangi legitimasi Islam di Eropa. Metodologi analisis kritis membantu peneliti untuk memahami isu utama, meninjau bukti-bukti masa lalu dan sekarang dari sumber terpercaya untuk membangun argumen konkret dalam memberikan evaluasi kritis pada masalah yang dibahas. Ini juga merupakan bentuk metode yang melibatkan penyelidikan topik lebih dalam, dengan menjangkau bagian bawah dari permukaan realitas untuk mengeksplorasi kebenaran dari masalah tertentu. Artikel itu menetapkan argumen melalui analisis sejarah di Eropa mulai dari zaman kuno untuk menyajikan situasi dan memberikan analogi yang jelas dan legitimasi di hadapan Islam di Eropa. Temuan ini menunjukkan bahwa Islam memang bagian dari Eropa sejak berdirinya kekhalifahan Umayyah dan kehadiran Islam di Sisilia. Selain itu, bersamaan dengan meningkatnya umat Islam, isu ateisme dan sekularisme merupakan bukti bahwa Eropa tidak lagi menjadi pusat Kekristenan tetapi sudah menjadi masyarakat multikulturalisme.